Artificial intelligence and orthopaedics - Dar, Tahir A.; Akhter, Zahida; Maajid, Abdul; Islam, Nasir Ul; Dhar, Shabir A.; Hamid, Hamza; Shabir, Anbreen (International Journal of Research in Orthopaedics, 2024)
Artificial intelligence is the next big thing in human history. It is set to affect large and small industries, entertainment, agriculture, literature, research, and healthcare. The field of Artificial intelligence includes machine learning and deep learning, which denote an increased level of specialization. These changes are also set to influence orthopedic trauma, from diagnostics, clinical assessment, surgical intervention, rehabilitation, and outcome prediction. Some of these fields will be affected more than others. We carried out a narrative review of artificial intelligence and orthopaedic surgery to provide an updated overview of the current and future applications. AI is set to revolutionize radiological diagnostics, outcome measurement, and rehabilitation in orthopedic trauma. However, concerns about clinical decision-making and intervention remain. Ethical concerns, regulation, and superiority over traditional methods of treatment also need to be assessed. Until then, the role of AI in orthopaedic trauma remains in the realm of possibilities.